Knowledge, attitude, and practices on COVID-19 prevention and diagnosis among medical workers in the radiology department: A multicenter cross-sectional study in China - Sun, Qiyuan; Yu, Chunyan; Zheng, Zhedong; Wu, Qiong; Zhang, Jian; Jiang, Peng; Liu, Ying (Frontiers in Public Health, 2023)
Objective The aim of this study was to investigate the knowledge, attitude, and practice (KAP) of medical workers in the radiology department toward the prevention and diagnosis of COVID-19. Methods This multicenter cross-sectional study was conducted among medical workers in the radiology department of 17 hospitals between March and June 2022. Results A total of 324 medical workers were enrolled. The mean knowledge scores were 15.3 ± 3.4 (out of 23), attitude scores were 31.1 ± 5.6 (range 8–40), and practice scores were 35.1 ± 4.4 (range 8–40). Positive attitudes (OR = 1.235, 95% CI: 1.162–1.311, P < 0.001) and aged 41–50 years were independently associated with higher practice scores. Those with the better practice were more likely to be older (OR = 2.603, 95% CI: 1.242–5.452, P = 0.011), nurses (OR = 2.274, 95% CI: 1.210–4.272, P = 0.011) and with junior/intermediary/vice-senior title (OR = 2.326, 95% CI: 1.030–5.255, P = 0.042; OR = 2.847, 95% CI: 1.226–6.606, P = 0.015; OR = 4.547, 95% CI: 1.806–11.452, P = 0.001, respectively). Subgroup analysis revealed significant differences in knowledge between technicians and physicians and nurses and between staff working in tertiary hospitals and non-tertiary hospitals. Knowledge is positively correlated with attitude (β = 0.54, P < 0.001), and attitude is positively correlated with practice (β = 0.37, P < 0.001). Attitudes significantly mediated the association between knowledge and practice (β = 0.119, P < 0.001). Conclusion The radiology medical workers showed moderate knowledge but good attitudes and practices of prevention and diagnosis of COVID-19. Attitudes were found to be positively associated with better practices of prevention and diagnosis of COVID-19. Attitudes significantly mediated the association between knowledge and practice.